Los actores de la economía social y solidaria en Bolivia: Dilemas de acción colectiva en el gobierno de Evo Morales - Fernanda Wanderley (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2020)
– The plurality of the Bolivian economy is a subject of analysis and discussion with a long history in Bolivia due to the persistence and coexistence of economic units other than the capitalist enterprise and the public sector. The period of the government of President Evo Morales (2005 and 2019) constitutionalized the plural economy model. Different groups were oriented to promote the new constitutional model of plural economy through the elaboration and approval of new laws. This document has two objectives. The first is to analyze the four types of economic organizations whose forms differ from private or public companies: peasant economic organizations (OECAS), community economic organizations (OECOM), artisan associations and cooperatives. It seeks to identify the characteristics of these economic organizations and their historical trajectories as political subjects. The second objective is to analyze the collective action promoted by these actors during Evo Morales' government and the political economy established in a context of exceptional economic boom. It investigates the factors that explain the difficulties for the construction of a common, consistent and integrated public policy agenda, towards the institutionalization of the plural economy. The analysis offers clues to understand the events that occurred between October and November 2019 that resulted in the fall of the Evo Morales government, specifically, on the reasons for the weak mobilization of these actors, who constituted the Government support base. This research was developed within the Instituto de Investigaciones Socio-Económicas de la Universidad Católica Boliviana, IISEC.
Keywords: 330; Social and Solidarity economy; Bolivia; Evo Morales Government; Collective Action; Plural Economy